Harmonic Multivalent Functions Defined by General Integral Operator - Raheam A. Al-Saphory; Mays S. Abdul Ameer; Abdul Rahman S. Juma (Al-Qadisiyah Journal of Pure Science, 2020)
The main aim of the present work is to introduce the class of multivalent harmonic functions defined by the general integral operator. Thus, We get some geometric properties, like coefficients estimate, extreme point and distortion theorem, convolution property, radii of starlikeness, and convexity.